Aromatic compounds depurative and plant growth promotion rhizobacteria abilities of Allenrolfea vaginata (Amaranthaceae) rhizosphere microbial communities from a solar saltern hypersaline soil - Rodríguez-Valdecantos, Gustavo; Torres-Rojas, Felipe; Muñoz-Echeverría, Sofía; del Rocío Mora-Ruiz, Merit; Rosselló-Móra, Ramon; Cid-Cid, Luis; Ledger, Thomas; González, Bernardo (Frontiers in Microbiology, 2023)
Introduction This work investigates whether rhizosphere microorganisms that colonize halophyte plants thriving in saline habitats can tolerate salinity and provide beneficial effects to their hosts, protecting them from environmental stresses, such as aromatic compound (AC) pollution. Methods To address this question, we conducted a series of experiments. First, we evaluated the effects of phenol, tyrosine, 4-hydroxybenzoic acid, and 2,4-dichlorophenoxyacetic (2,4-D) acids on the soil rhizosphere microbial community associated with the halophyte Allenrolfea vaginata. We then determined the ability of bacterial isolates from these microbial communities to utilize these ACs as carbon sources. Finally, we assessed their ability to promote plant growth under saline conditions. Results Our study revealed that each AC had a different impact on the structure and alpha and beta diversity of the halophyte bacterial (but not archaeal) communities. Notably, 2,4-D and phenol, to a lesser degree, had the most substantial decreasing effects. The removal of ACs by the rhizosphere community varied from 15% (2,4-D) to 100% (the other three ACs), depending on the concentration. Halomonas isolates were the most abundant and diverse strains capable of degrading the ACs, with strains of Marinobacter, Alkalihalobacillus, Thalassobacillus, Oceanobacillus, and the archaea Haladaptatus also exhibiting catabolic properties. Moreover, our study found that halophile strains Halomonas sp. LV-8T and Marinobacter sp. LV-48T enhanced the growth and protection of Arabidopsis thaliana plants by 30% to 55% under salt-stress conditions. Discussion These results suggest that moderate halophile microbial communities may protect halophytes from salinity and potential adverse effects of aromatic compounds through depurative processes.